Customer preferences in purchasing residential property: an interview survey / Norhayati Omar ... [et al.] - Omar, Norhayati; Shaik Alaudeen, Muharratul Sharifah; Abdul Munir, Zarina; Abd Malik, Shaherah; Abd. Rahman, Nor Diana (UiTM Cawangan Johor, 2019)
The economic crisis has prompted a pressing need for the housing property sector to enhance sales. Many developers face obstacles in catering the increasing demand and different customer tastes. Developers must deliver customer demands or risk experiencing losses and poor sales. The current study conducted an interview survey of 10 customers among chosen developer organizations in the Klang Valley. Analysis of the responses indicated that facilities, investment and location are what customers prioritize when choosing property. They also show a preference for condominiums and landed homes. These results suggest that developers must continue to apply relevant tactics in managing customer demands.